IMPLEMENTASI PENDIDIKAN AGAMA DI SEKOLAH MENENGAH KEJURUAN (SMK) BAKTI PANGKALPINANG BANGKA BELITUNG - Qowaid, Qowaid (Badan Litbang dan Diklat Kementerian Agama RI, 2017)
AbstractReligious education in schools must be given to students in accordance with the religion adopted and taught by teachers of the same religion. Religious education for children is also one form of implementation of human rights. Many schools have implemented in accordance with the rules. However, several schools, especially privateÂ schools, have not implemented religious education in schools in accordance with the regulations. This research is trying to know the implementation of religious education in private schools, in thisÂ case, Vocational High School Bakti Pangkalpinang Bangka Belitung. The results show that Buddhist, Christian, Catholic, Islamic, and Buddhist Education have been implemented in Bakti Vocational High School (SMK) Pangkalpinang according to the religion of the students. However, Confucian Religion Education has not been implemented in this School.Â AbstrakPendidikan Agama di sekolah wajib diberikan kepada peserta didik sesuai dengan agama yang dianut dan diajar oleh guru yang seagama. Pendidikan agama bagi anak juga merupakan salah satu bentuk implementasi hak asasi manusia. Banyak sekolah telah mengimplementasikan sesuai dengan peraturan. Namun masihtidak sedikit sekolah, khususnya sekolah swasta, yang belum mengimplementasikan pendidikan agama di sekolah sesuai dengan ketentuan. Penelitian ini berusaha mengetahui implementasi pendidikan agama di sekolah swasta, dalam hal ini, Sekolah Menengah Kejuruan Bakti Pangkalpinang Bangka Belitung. Hasil penelitian menunjukkan bahwa Pendidikan Agama Buddha, Kristen, Katholik, Islam, dan telah diimplementasikan di Sekolah Menengah Kejuruan Bakti (SMK) Pangkalpinang sesuai agama yang dipeluk peserta didik. Adapun Pendidikan Agama Konghucu belum diimplementasikan di Sekolah ini.